Firm sponsored training and productivity in Morocco - Sekkat, Khalid (2011)
Using a sample of around 300 large and small firms covering six industries in Morocco, the article investigates the relationship between a firm's training decision in 1999 and labour productivity in subsequent years. The analytical framework allows output to depend on unobserved-time-invariant firm characteristics and assumes that technical progress depends on training. Controlling for unobserved heterogeneity among firms and correcting for potential self-selection and endogeneity bias, the estimation shows that the intensity of training has a significant and positive impact on productivity in small and medium enterprises. The finding is robust to the introduction of various control variables. - Reproduced.
Keywords: Training - Morocco; Training